AuNPs for identification of molecular signatures of resistance - Veigas, Bruno; Fernandes, Alexandra R.; Baptista, Pedro V. (Frontiers in Microbiology, 2014)
The increasing levels of drug resistance are one of biggest threats to overcome microbial infection. The ability to rapidly and accurately detect a given pathogen and its drug resistance profile is essential for the appropriate treatment of patients and for preventing further spread of drug-resistant strains. The predictive and informative value of these molecular markers needs to be translated into robust surveillance tools that correlate to the target and extent of resistance, monitor multiresistance and provide real time assessment at point-of-need. Rapid molecular assays for the detection of drug-resistance signatures in clinical specimens are based on the detection of specific nucleotide sequences and/or mutations within pre-selected biomarkers in the genome, indicative of the presence of the pathogen and/or associated with drug resistance. DNA and/or RNA based assays offer advantages over phenotypic assays, such as specificity and time from collection to result. Nanotechnology has provided new and robust tools for the detection of pathogens and more crucially to the fast and sensitive characterisation of molecular signatures of drug resistance. Amongst the plethora of nanotechnology based approaches, gold nanoparticles have prompt for the development of new strategies and platforms capable to provide valuable data at point-of-need with increased versatility but reduced costs. Gold nanoparticles, due to their unique spectral, optical and electrochemical properties, are one of the most widely used nanotechnology systems for molecular diagnostics. This review will focus on the use of gold nanoparticles for screening molecular signatures of drug resistance that have been reported thus far, and provide a critical evaluation of current and future developments of these technologies assisting pathogen identification and characterisation.